Multiple RNase H activities in mammalian type C retravirus lysates. - Gerard, G F (1978)
Lysates of Moloney murine sarcoma-leukemia virus [M-MSV(MLV)], a virus complex grown in the rat cell line 78A-1, were found to contain three RNase H species separable by polycytidylic acid[poly(C)]-agarose chromatography. RNase H activity (RNase H I) associated with RNA-directed DNA polymerase eluted at 0.23 M KCI from poly(C)-agarose. RNase H II, which eluted from poly(C)-agarose at 0.12 M KCI and was not associated with DNA polymerase activity, was shown to be identical to an RNase H species (designated RNase H II) previously isolated from M-MSV(MLV) by a different procedure (G. F. Gerard and D. P. Grandgenett, J. Virol. 15:785-797, 1975). M-MSV(MLV) RNase H II was established to be a random exohybridase that requires free-chain termini in its hybrid substrate for activity. Lysates of Rickard feline leukemia virus also contained RNase H activity not associated with DNA polymerase activity that eluted from poly(C)-agarose at 0.12 M KCl. A third species of enzyme from M-MSV(MLV) lysates, called RNase H III, did not bind to poly(C)-agarose in 0.06 M KCl. RNase H III was purified from lysates of M-MSV(MLV) and M-MLV (grown in mouse cells) by sequential chromatography on poly(C)-agarose, DEAE-cellulose, phosphocellulose, and polyuridylic acid-Sepharose. Purified RNase H III (i) was free of any associated DNA polymerase activity, (ii) had an apparent molecular weight of 30,000 determined by Sephadex G-100 gel filtration, (iii) had an absolute requirement for Mn2+ (1 mM optimum) for the degradation of [3H](A)n.(dT)n, (iv) was inhibited by the presence of any salt in reaction mixtures, and (v) was endoribonucleolytic in its mode of action as indicated by the size distribution of limited degradation products of [3H](A)n.(dT)n. RNase H III was inhibited by antisera prepared against Rauscher MLV and simian sarcoma virus reverse transcriptase, and the quantity of RNase H III and RNase H I present in lysates of M-MLV were reduced and increased proportionately if virus was lysed in the presence of the protease inhibitor phenylmethylsulfonyl fluoride. These results indicate that RNase H III is a proteolytic cleavage product of DNA polymerase-RNase H. Substantial RNase H activity that did not bind to poly(C)-agarose in 0.06 M KCl was also found in lysates of Harvey MSV(MLV), Rauscher MLV, and Rickard feline leukemia virus, but not in lysates of avian myeloblastosis virus.